PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE PADA MINAT PENGGUNAAN INTERNET BANKING DENGAN ATTITUDE TOWARD USING SEBAGAI VARIABEL INTERVENING - Bangkara, Rajendra Prasada; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
The use of internet technology banking is a way to perform banking transactions using the Internet network that allows customers to transact. The purpose of this study was to determine the effect of perceived usefulness and perceived ease of use, the interest (intention) the use of internet banking with an attitude (attitude toward using) as an intervening variable. The study was conducted on SME trading business in Denpasar as it has a number of MSMEs biggest trading business in Bali. Samples are taken by 92 companies using the formula Slovin. Data collection techniques used in this study was a questionnaire and data analysis techniques using path analysis techniques. Based on the analysis found that the variables of perceived usefulness, perceived ease of use, and attitude toward using a positive effect on the interest in the use of internet banking.
Keywords: Perceived Usefulness, Perceived Ease Of Use, Attitude Toward Using, Interests (Intention), Internet Banking, SMEs